Posttraumatic Fat Necrosis Presented as Cellulitis of the Leg - Einat Haikin Herzberger; Shraga Aviner; Evgenia Cherniavsky (Case Reports in Pediatrics)
Cellulitis, a diffuse inflammation of connective tissue with severe inflammation of dermal and subcutaneous layers of the skin, is a common lesion in children, usually responsive to systemic antibiotic therapy. However, an unusual course of healing or some nontypical features should call the treating physician to consider and investigate for other diagnoses that might prevent unnecessary treatment and alleviate parental stress. We present a case of posttraumatic fat necrosis, demonstrating some pitfalls in the process of diagnosis.